Effectiveness of Interactive Teaching Methods on Students’ Performance in Social Studies and Civic Education: An Experimental Study in Nigerian Secondary Schools - Matthew Damilola Omojemite (Journal of Research in Social Sciences and Language)
This study investigates the effectiveness of interactive teaching methods on students’ academic performance in Social Studies and Civic Education in Nigerian secondary schools. The study adopted a quasi-experimental research design with a control group. The population consisted of 85,121 Junior Secondary School students from public secondary schools in Southwest Nigeria. A sample of 200 students was selected using a multistage sampling method involving both random and purposive sampling techniques. Two instruments, Social Studies Performance Test (SSPT) and Civic Education Performance Test (CEPT), were developed for data collection. Experts in Social Studies, Civic Education, and Educational Measurement validated the instruments. The reliability was established using the test-retest method, yielding reliability coefficients of 0.89 for SSPT and 0.84 for CEPT. The instruments were administered through pre-tests and post-tests after instructional interventions. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (t-test analysis and Regression ANOVA). Findings revealed that interactive teaching methods significantly improved students’ academic performance in both subjects compared to traditional teaching methods. Additionally, demographic factors such as gender, location, and age did not significantly influence student performance. It was recommended that teachers adopt student-centered teaching strategies, while policymakers should integrate interactive methods into curricula to enhance learning outcomes across diverse student demographics.